Sliding frictional contact of one dimensional hexagonal piezoelectric quasicrystals coating on piezoelectric substrate with imperfect interface. (15th March 2022) - Huang, Rukai; Ding, Shenghu; Chen, Qiwenli; Lv, Chaofan; Zhang, Xin; Li, Xing
Abstract: This paper studied the sliding frictional contact of a one-dimensional (1D) hexagonal piezoelectric quasicrystals (PEQCs) coating, where the PEQCs coating is imperfectly bonded to a transversely isotropic piezoelectric (PE) substrate. The frequency response functions (FRFs) of displacements and stresses of phonon (phason), electric potentials and electric displacements, are analytically derived by applying double Fourier integral transforms to the general solutions and boundary conditions of the 1D hexagonal PEQCs coating-PE substrate systems. The conjugate gradient method (CGM) is used to obtain the unknown pressure distribution and the discrete convolution-fast Fourier transform technique (DC-FFT) is involved to calculate the contact responses such as displacements and stresses. Numerical results are given to reveal the influences of coating thickness, loading conditions and imperfection indices on the contact behavior, which provide a reference basis for PEQCs coating experimental analysis and intelligent structures (systems) design.